1994
DOI: 10.1149/1.2059335
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorous Acid Impurities in Phosphoric Acid Fuel Cell Electrolytes: II . Effects on the Oxygen Reduction Reaction at Platinum Electrodes

Abstract: The effects of phosphorous acid additions on the oxygen reduction reaction at platinum electrodes in concentrated phosphoric acid were studied. The oxygen reduction currents decreased, and the Tafel slopes became more negative upon the addition of small concentrations of phosphorous acid. In addition, the phosphorous acid oxidation current tended to compete with the oxygen reduction current. These effects became more pronounced at higher phosphorous acid concentrations and at higher temperatures. Upon the addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 2 publications
3
14
0
Order By: Relevance
“…[10][11][12] The peak appears around 0.70 V, the same potential observed by Vogel and Barris. 10 Similar behavior was observed by Sugishima 13 for high temperatures. In order to remove the impurities, the H 3 PO 4 was further purified, but the adopted treatment did change considerably this behavior.…”
Section: Resultssupporting
confidence: 80%
“…[10][11][12] The peak appears around 0.70 V, the same potential observed by Vogel and Barris. 10 Similar behavior was observed by Sugishima 13 for high temperatures. In order to remove the impurities, the H 3 PO 4 was further purified, but the adopted treatment did change considerably this behavior.…”
Section: Resultssupporting
confidence: 80%
“…This may include the oxidation of the alkyl chain [54±56] and, especially in the case of S-C7, also the oxidation of products from the previous reduction of the sulfonic acid group [53]. This behavior has already been observed for methanesulfonic acid [55] and phosphorous acid impurities in phosphoric acid [57,58], but is not fully understood yet. For I-C7, irreversible electrochemical oxidation is observed for potentials E > 1.0 V only [24].…”
Section: Stability and Reactivitymentioning
confidence: 99%
“…Although the kinetics of these processes in a H 3 PO 4 environment have been the subject of several studies, the processes are not yet fully understood, [5][6][7]. Several authors have observed the presence of one or more oxidation peaks in the double layer region of cyclic voltammograms recorded in concentrated H 3 PO 4 at elevated temperatures on a bulk Pt electrode [8][9][10][11]. These peaks were ascribed to the oxidation of adsorbing impurities that can be removed by treating H 3 PO 4 solution with H 2 O 2 and that form on the electrode surface at potentials of hydrogen underpotential deposition and evolution.…”
Section: Introductionmentioning
confidence: 99%
“…The exact nature of these impurities has been a subject of discussion for a long time. Lower phosphorus oxoacids and elemental phosphorus in the form of Pt-P have been put forward as solutions [9,10]. Later, Sugishima et al showed that concentrations of H 3 PO 3 in the order of 10 À3 mol dm À3 in the electrolyte at room temperature led to a decrease in O 2 reduction current density and a substantial increase in the Tafel slope of the reaction.…”
Section: Introductionmentioning
confidence: 99%